Analysis on the Trend of Mobile Device Software Development - Baiqing Liang; Yingqi Wei; Xuan Luo (Dianxin kexue)
Intelligence of mobile device has brought the rapid evolution of the terminal system and application software，and operation system infrastructure software is continuously renovated and combining the native application environment with web applications ecological environment. Mobile application is developing from porta1-type towards the direction of segmentation market and the specialty orientation. The mobile device operating system，application software development status and direction of evolution were summarized and analyzed.